Metamorphosis and identity - Bynum, Caroline Walker (Zone Books, 2001)
Introduction: Change in the Middle Ages. The Ulster werewolves ; Change: the concept ; Change and the twelfth century ; Hybrid and metamorphosis ; Some methodological considerations -- I. Wonder. Recent scholarship on wonder and wonders ; The many wonder discourses of the Middle Ages ; Theological and philosophical discussion ; Admiratio in devotional literature ; The marvelous in literature of entertainment ; The range of wonder responses ; Wonder and significance ; Wonder as cognitive, perspectival, and non-appropriative ; Wonder and the modern historian -- II. Metamorphosis, or Gerald and the werewolf. Again the question of bodily change ; Ovidian poetry as fascination with change ; Theological speculation on growth and change ; Werewolf stories as testing of boundaries ; The Ovid reception as enthusiasm for order ; Learned theology and miracle stories as ontological control ; Were medieval werewolves really metempsychosis? ; Conclusion -- III. Monsters, medians, and marvelous mixtures: hybrids in the spirituality of Bernard of Clairvaux. Mixture and monster ; Similitude and doubleness ; Change and unitas ; Natural philosophy as the context of Bernard's understanding ; Twelfth-century religious life as context ; Literature and art as context ; Conclusion: Hybridity in the spirituality of Bernard of Clairvaux -- IV. Shape and story. The problem of personal identity ; Some stories about werewolves: Ovid's Lycaon ; Some stories about werewolves: Marie de France's Bisclavret ; Stories about werewolves and metamorphosis: Angela Carter ; Metamorphosis and identity ; Shape and story, body and narrative ; Metamorphosis in Dante ; Conclusion -- Afterword